Cheeseman, Betty. Interview about growing up in Petty Harbour. - Barrett, Terra (2014)
Interview with Betty Cheeseman focuses on growing up in Petty Harbour, children's games and activities, community events, and the influence of music in Betty's life. Introductions; Betty Cheeseman (nee Clarke) was born in Petty Harbour in 1954; Cheeseman grew up in Petty Harbour and remained in the community until she married in 1979; 0:34 - Children’s games and activities; Growing up in Petty Harbour; 2:30 - Cheeseman’s family; 3:36 - Families in Petty Harbour; Visiting Petty Harbour; 4:36 - Concerts; Doyle family; Heritage days; Keeping tradition alive; 6:05 - Winter ice in the harbour; Jumping ice pans; 7:10 - Spreading fish on the flakes; 8:27 - Cheeseman’s father’s work; 9:15 - School; 10:28 - Mrs. Irene Cove’s store in Petty Harbour as a hangout spot; 12:21 - Climbing the hills of Petty Harbour; 13:12 - Playing behind the powerhouse; 14:06 - Swimming; Homemade bread; 16:27 - Christmas baking; Christmas in Petty Harbour; Christmas visiting; Cheeseman’s mom playing the accordion; 19:25 - The songs her mom would play; Step dancing; 19:55 - Concerts; Music; 21:13 - Learning the accordion; Singing; Dancing; 22:26 - Cheeseman’s Mom learning the accordion; 23:31 - Her brother learning the guitar in the sanatorium; Visiting her brother in the sanatorium; 26:31 - Her father dancing; Musical influence from both parents; 26:56 - Style of dancing; Playing instruments; 28:30 - Sunday visits at Cheeseman’s family’s house; Card games; 31:12 - Christmas concerts and children’s concerts; Adults' concerts; Renewal of St. Patrick’s day concert in Petty Harbour; Doyle’s family influence; 33:35 - St. Joseph’s school and church; Confirmation; 35:26 - Role of religion in upbringing; Sunday as an important day; Sunday traditions; 38:39 - Garden parties; Garden party dances; 43:47 - Family stories; Visiting grandparents in Maddox Cove; Household chores; 47:20 - Gardening/livestock; Material culture--grandmother’s dishes; 51:43 - Learning how to dance from her oldest brother; 52:29 - Household chores; Cleaning the house on ...